Development of Technology of Suspension Polymerization of Propylene at "Tomskneftekhim" Company - Mayer E. A.; Pestryakov A. N. Aleksey Nikolaevich; Klimov I. G.; Dudchenko V. K. (2012, 2012)
Selected, peer reviewed papers from the 2012 Spring International Conference on Material Sciences and Technology (MST-S), May 27-30, 2012, Xi'an, China